Alcuni rilievi sulla lingua dei dibattiti parlamentari - Orrù, Paolo (Verbum – Analecta Neolatina, 2019)
The analysis of political language has been a consistent reality for many years in Italian linguistic studies. Since the early studies of Paola Desideri (1984), the attention to pragmatic aspects has been central to the discipline. The object of this contribution will be the parliamentary debates, as rendered in their official transcription. We gathered a small corpus (around 850 thousand words) from various periods that have distinguished Italian parliamentary history. Assuming as a starting point the first parliament of the Kingdom of Italy and moving towards the present day, we have decided to examine some pragmatic characteristics of these texts and verify the most recent developments. The study presents the fundamental objective of combining the analysis of political discourse in a diachronic pragmatics perspective to the methodological approach of corpus linguistics (through various tools, such as frequency lists, concordance lines, collocations) in order to investigate forms of the interaction between members of the Parliament, and the persistence in the texts of some of the aspects of spoken language.